To stay or go: movement, behavior, and habitat use of shortfin mako sharks (Isurus oxyrinchus) in the Gulf of Mexico - Gibson Banks, Kesley; Coffey, Daniel M.; Fisher, Mark R.; Stunz, Greg W. (Frontiers in Marine Science, 2025)
Shortfin mako sharks (Isurus oxyrinchus) are apex predators in marine ecosystems, yet the North Atlantic stock has declined drastically. Despite their imperiled status, limited research has focused on the movement and habitat use of mature individuals in the Gulf of Mexico (also known as Gulf of America; hereafter Gulf), a region hypothesized to serve as gestation and parturition grounds. From 2016 to 2021, 21 mako sharks (90% mature or nearing maturity) were satellite-tagged in the northwestern Gulf to evaluate habitat suitability, move persistence, and the environmental drivers influencing these patterns. This study revealed year-round habitat use in the Gulf, particularly in the northwestern Gulf west of the central stem of the Mississippi River delta (~89.1°W), identifying this area as a previously unrecognized important habitat. Mako sharks exhibited resident behavior in productive shelf and shelf-slope waters and at sea surface temperatures (SSTs) between 19.6°C and 26°C, while transiting behavior was observed at SSTs >26°C and in migration corridors, such as the Loop Current, during movements through the Yucatán Channel or Straits of Florida. These findings highlight intra-population variability in movement and emphasize the need to manage these highly migratory species at the ocean-basin scale. Developing spatially explicit models that incorporate regional connectivity and environmental drivers will be essential for improving management strategies and rebuilding efforts for this vulnerable species.